2019
DOI: 10.1002/qre.2524
|View full text |Cite
|
Sign up to set email alerts
|

Robustness of response surface designs to missing data

Abstract: In this paper, minimax loss response surface designs are constructed. These designs are more robust to one missing design point than the original designs. The proposed designs are compared with the designs in the literature, and they are better in terms of loss and number of runs. Moreover, the new suggestion for the value of generates designs not only with less losses but also with higher D-efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…A central composite design was used to develop a second order polynomial equation to best represent the response model. In the present investigation, CCD was preferred over BBD for optimization due to its robust nature and inclusion of factors at extreme settings, thus generating best fit model (Aanchal et al, 2016;Alrweili et al, 2019). Multiple shoot initiation was observed when the explants were inoculated in certain media composition as per the experimental design.…”
Section: Response Surface Methodology For Optimizationmentioning
confidence: 96%
“…A central composite design was used to develop a second order polynomial equation to best represent the response model. In the present investigation, CCD was preferred over BBD for optimization due to its robust nature and inclusion of factors at extreme settings, thus generating best fit model (Aanchal et al, 2016;Alrweili et al, 2019). Multiple shoot initiation was observed when the explants were inoculated in certain media composition as per the experimental design.…”
Section: Response Surface Methodology For Optimizationmentioning
confidence: 96%
“…Furthermore, Ahmed (2014) studied the 'missing values estimation comparison in split-plot design' which shows that one missing value obtains the same estimates, while two or three missing values show that the Coons method is the best. In their work Alrweili, et. al (2019) suggested that Akhtar and Prescot (1986) applied the Minimax loss criterion to evaluate and generate CCDs, which, when applied to a classical CCD with four factors, generated 26 runs.…”
Section: Introductionmentioning
confidence: 97%
“…The equation that is generated as a result of the removal of some parameters in a standard model is called a non-standard model (Myers et. al 2009;Iwundu and Jaja 2017;Alrweili et. al 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On a related theme, Alrweili et al propose a minimax loss response surface design which is robust to observation loss when compared to similar designs in the literature. Han develops an optimal design for accelerated life testing of manufactured products. Various optimality criteria for the design are considered, and the existence of the optimal designs is investigated for exponential lifetimes with a single stress variable …”
mentioning
confidence: 99%